Determining Profitable Annual Forage Rotations - J. D. Holman; T. Roberts; S. Maxwell (Kansas Agricultural Experiment Station Research Reports, 2015)
Producers are interested in growing forages, yet the southwest region of Kansas lacks proven recommended crop rotations such as those for grain crops. Forage production is important to the region’s livestock and dairy industries and is becoming increasingly important as irrigation well capacity declines. Forages require less water than grain crops and may allow for increased cropping intensity and opportunistic cropping. A study was initiated in 2013 comparing several 1-, 3-, and 4-year forage rotations with no-till and minimum-till (min-till). Data presented are from 2013 through 2014. Winter triticale yields were not affected by tillage in 2013 but were increased by tillage in 2014. Double-crop forage sorghum yielded 30% of full-season forage sorghum in 2013, which was a drought year, but across years yielded 70% of full-season sorghum. Oats failed to make a crop during the drought year and do not appear to be as drought tolerant as spring triticale or forage sorghum. Subsequent years will be used to compare forage rotations and profitability.
Keywords: forage rotations; cropping systems; tillage systems; forage; forage quality; water use efficiency